2017
DOI: 10.1186/s12906-017-1891-0
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the combined extracts of Herba Epimedii and Fructus Ligustrilucidi on airway remodeling in the asthmatic rats with the treatment of budesonide

Abstract: BackgroundAsthma is characterized by chronic airway inflammation, leading to structura1 changes in the airway, collectively termed airway remodeling. Airway remodeling is thought to contribute to airway hyper responsiveness and irreversible airflow limitation. The combination of Herba Epimedii (HE) and Fructus Ligustri Lucidi (FLL) decoction and the systemic administration of glucocorticoids (GC) had a synergistic inhibitory action on airway inflammation in the asthmatic model rats. However, the effects of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 58 publications
2
30
0
Order By: Relevance
“…Budesonide is the most commonly used inhaled GC. Several studies have indicated that atomized budesonide can inhibit the increase in eosinophils, TNF-α, IL-4, IL-5, IL-13, and TGF-β 1 in the BALF of OVA-sensitized rats or mice, and thereby further alleviate airway in ammation and reduce airway remodeling [36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Budesonide is the most commonly used inhaled GC. Several studies have indicated that atomized budesonide can inhibit the increase in eosinophils, TNF-α, IL-4, IL-5, IL-13, and TGF-β 1 in the BALF of OVA-sensitized rats or mice, and thereby further alleviate airway in ammation and reduce airway remodeling [36][37].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, inhaled cortiand asthma control. The use of complementary and alternapatients [44] - [45][46][47] -- [48][49][50] - [15,19,51] -Acknowledgements o 81373424, 81573438, o Author contribution -…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, the leaves of E pimedium had long been used as a kidney tonic and antirheumatic for more than 2000 years [ 19 ]. In recent years, it was also used to treat various diseases, such as parkinson’s disease [ 20 ], rheumatic arthritis [ 21 ], osteoporosis [ 22 , 23 ] and asthma [ 24 ]. Virtually, most of the attention focused on E .…”
Section: Discussionmentioning
confidence: 99%